Mathematical model of friction wear process on the example of polymer composites on the basis of phenol-formaldehyde resins - Tretyakov, A.O. (Polimery, 2022)
Mathematical expression allowing calculation of temperature (T) in the friction zone was found by use of similarity theory and dimensions analysis. This temperature is a criterion of abrasion estimation [friction (abrasive) wear]. The model has been elaborated and on its basis one can calculate T value of any element being a part of friction pair. The condition of usefulness of a model is being familiar with mechanical and thermal characteristics of a polymer composite as well as its work conditions.